Pluralidad ciudadana y unidad del cuerpo político: Desafíos y dilemas de la soberanía popular en los inicios del siglo XIX (Ágora Journal, 2020)
This article is a brief exercise of reflection on some of the dilemmas that opened the coexistence of the two devices of modern political organization: electoral representation and the principle of division of powers. These dilemmas were common to the political experiments tested in the new sovereign communities that emerged from the collapse of empires. To illustrate them, the case of the Río de la Plata is analyzed at two successive moments in the first half of the 19th century. The objective of the exercise is to recreate through the periodic press the political environments and the horizons of ideas that crossed both moments to exhibit the different responses that were tried in the face of post-revolutionary challenges.